Caracterização clínica epidemiológica e geográfica da hanseníase em município hiperendêmico do Brasil - Marciano, Lúcia Helena Soares Camargo [UNESP] (2015)
The objective of this study was to identify a pattern of spatial distribution of leprosy cases from 2000 to 2010, in the Rondonópolis municipality and its relationship with clinical epidemiological aspects of the disease. The Geographic Information System (GIS), ArcGIS 9.3, was used to determine the spatial location of 1,832 new cases and prepare thematic maps. MapInfo program, version 7.8, was used for geocoding the leprosy cases. Cluster analysis was carried out using the spatial analysis methodology, scan statistics (Scan). The cartographic databases and population census data of 2000 and 2010 from IBGE were used. Therefore, the analysis was performed in two periods, 2000 to 2005 and 2006 to 2010. The digital cartographic database of Rondonópolis addresses and the software ArcGIS 9.3 were used in order to build the new cases spatial clusters maps stratifying the cases as paucibacillary leprosy, multibacillary leprosy and disease in children under 15 years and the total population. Socioeconomic indicators were mapped according to coropletic cartographic technique. The analysis in all stratified populations revealed an overall reduction in the detection rate and increase in high-risk spatial clusters in all stratified populations. In addition a marked change was observed in the distribution of high and low risk groups and in detection high risk cluster in children under 15 years in the period of 2006 to 2010, signaling recent illness and presence of active focus of disease, besides an overlap of high-risk group of the multibacillary population with disease in children under 15 years. The findings show that leprosy remains a public health problem in the entire municipality, with demonstration of spatial high-risk areas that evidence the need of intensifying actions and definition of priority strategies for active search of leprosy cases